Prognostic performance of the SCAI shock classification at admission and during ICU treatment: a retrospective, observational cohort study - Britsch, Simone; Britsch, Markward; Hahn, Leonie; Langer, Harald; Lindner, Simon; Akın, Ibrahim; Helbing, Thomas; Dürschmied, Daniel; Becher, Tobias (Heart & lung, 2024)
Background - Cardiogenic shock (CS) is characterized by high mortality and requires accurate prognostic tools to predict outcomes and guide treatment. The Society for Cardiovascular Angiography and Interventions (SCAI) shock classification indicates shock severity and can be used for outcome prediction. - Objective - Here, we compare the prognostic performance of SCAI shock classification determined on admission and during intensive care unit (ICU) stay. - Methods - We included all patients with CS or conditions associated with developing CS based on ICD codes. SCAI shock stages were determined on admission and during the first 5 days of ICU stay. Receiver operating curves were used to compare the prognostic performance of SCAI stages on admission, SCAI stages during ICU stay and CS evolution (absent, resolved, persistent and new onset) for in-hospital mortality. - Results - Between 01/2018 and 06/2022, 1303 patients were identified and 862 patients were included. On admission, 50.6 % patients had SCAI shock stage A, 3.9 % SCAI shock stage B, 17.7 % SCAI shock stage C, 7.0 % SCAI shock stage D and 20.8 % SCAI shock stage E. Shock stage distribution changed dynamically during ICU stay. Compared to SCAI stage on admission (AUC 0.80; 95 % CI 0.77-0.83), highest achieved SCAI stage during ICU (AUC 0.86, 95 % CI 0.83-0.89, p < 0.0001) and shock evolution (AUC 0.87, 95 % CI 0.85-0.90, p < 0.0001) yielded better prognostic performance. - Conclusions - SCAI shock stages changed dynamically during ICU stay, and prognostic performance can be improved by considering highest achieved SCAI shock stage as well as the evolution of CS compared to SCAI shock stage on admission.
Online verfügbar: 25. Juni 2024, Artikelversion: 25. Juni 2024
Gesehen am 25.11.2024